IMPLEMENTASI KEBIJAKAN PROGRAM KAMPUNG IKLIM (PROKLIM) DI KELURAHAN TOBEK GODANG KECAMATAN BINAWIDYA KOTA PEKANBARU TAHUN 2020 - Suci Fitria; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The background of this research is the lack of human resource empowerment in implementing climate change adaptation and mitigation actions, then the author's interest in ProKlim in Tobek Godang Village which is the only village that has succeeded in realizing ProKlim from 83 Kelurahan in Pekanbaru. This study aims to find out how the implementation of the ProKlim policy in  Tobek Godang Village, Binawidya District, Pekanbaru City in 2020. This study uses a qualitative descriptive approach. This research was conducted in the Climate Village, Tobek Godang Village and at the Riau Province Environment and Forestry Service. The data used in this study are primary and secondary data.This research uses the theoretical framework of policy implementation according to Van Meter and Horn. The results of this study indicate that the implementation of the ProKlim policy in Tobek Godang Village has been running and is well implemented, although there are still constraints on human resources, especially in community groups in the adaptation and mitigation action of ProKlim in Tobek Godang Village. The standard targets and policies for ProKlim in Tobek Godang Village have good commitment and motivation in implementing the ProKlim policy in Tobek Godang Village, the main tasks and functions have been carried out in accordance with the SOPs contained in the Regulation of the Director General of Climate Change Control at the Ministry of Environment and Forestry No. 4 of 2021 concerning guidelines for the implementation of ProKlim and in accordance with the vision and mission of the Governor of Riau in supporting the Green Riau Program. In general, this policy has succeeded in providing significant changes to the environmentally friendly ProKlim activities in Tobek Godang Village, especially RW 02.Keywords: Implementation, Policy, Climate Village Program (ProKlim)